2005
DOI: 10.1097/01.gme.0000163869.89878.d9
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of the predictors of prevalence and severity of symptoms commonly associated with menopause

Abstract: Sexuality and vasomotor symptom constructs seem to be more related to menopause than other constructs. The frequency of other constructs in the pre-menopause and their very strong association with increasing age suggest caution in attributing these factors directly to neuroendocrine events of the menopause transition. The strong associations between smoking and body size with symptoms, particularly vasomotor symptoms, suggest that interventions directed at these personal characteristics might be effective in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
57
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 20 publications
5
57
2
Order By: Relevance
“…In these analyses, we confirmed findings from previous studies, such as the strong, positive, independent association between body mass and incontinence [28,40,41]. The association between body mass and incontinence, as well as the association between smoking and irritability, provide additional data to support what is already known about the adverse effects of smoking and high body mass on health among midlife women and those who are aging.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In these analyses, we confirmed findings from previous studies, such as the strong, positive, independent association between body mass and incontinence [28,40,41]. The association between body mass and incontinence, as well as the association between smoking and irritability, provide additional data to support what is already known about the adverse effects of smoking and high body mass on health among midlife women and those who are aging.…”
Section: Discussionsupporting
confidence: 89%
“…First, there are large differences in the characteristics of the populations under study; for example, Ford et al [28] enrolled women at a younger age than our study and did not exclude hormone therapy users, as we did. Another potential explanation for the conflicting results is that data and blood collection in our study was not timed to a particular day or phase of the menstrual cycle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…63,64 The latter model is questioned by the findings of a case-control study by Gallicchio et al 65 and a cross-sectional study by Schilling et al, 66 who found significantly lower levels of estrogen in obese women (BMI 35 kg=m 2 , BMI >30 kg=m 2 , respectively) compared with normal-weight midlife women (BMI <25 kg=m 2 ). Similarly, other studies indicate that higher BMI 10,52,54,65,67,68 and a higher percentage of body fat 63,69 are associated with increased odds of reporting VMS. Although there is greater evidence in support of the thermoregulatory model than the thin hypothesis, it cannot solely explain the pathogenesis of HFs.…”
Section: Body Mass Index and Obesitymentioning
confidence: 79%
“…Some symptoms associated with changing hormone levels are directly linked with estrogen depletion. Hot flashes, night sweats, and vaginal atrophy resulting in vaginal dryness are correlated with changing levels of sex hormones [7] . Other symptoms, such as sleep disturbances, fatigue, anxiety, and weight gain, although common to the experience of menopause, are multi factorial in cause and occur in non-postmenopausal women as well [8] .…”
mentioning
confidence: 99%